CAUSES AND ECONOMETRIC ANALYSIS OF IMPAIRMENT OF INNOVATION COMPETENCES ACROSS THE REGIONS (Marketing Journal, 2025)
This article analyzes the disparities in the level of innovation potential across regions using economic -statistical and econometric approaches. The study considers innovation potential as a key driver of regional economic development and 577 scientifically substantiates that its uneven distribution across regions significantly impacts economic growth rates, competitiveness, and social well -being. Statistical indices, variation indicators, and econometric models are used to identify differences in innovation potential, revealing interregional disparities and their underlying factors. The results of the research provide a scientific and practical basis for improving regional innovation policy, reducing interregional imbalances, and ensuring balan ced innovation -driven development.
Keywords: innovation potential; regional development; territorial inequality; economic -statistical analysis; econometric analysis; Gini index; Theil index; panel data; innovation policy; interregional disparities